Composite board and preparation method thereof
By using phase change functional aggregate for heat storage decorative panels and compounding them with aerogel insulation gel layer, the problem of the lack of constant temperature, decoration and multiple synergies in existing building thermal insulation composite panels is solved, and excellent mechanics is achieved Performance constant temperature, heat insulation and decorative composite panels.
Patent Information
- Application Number
- CN202411477771.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-07
AI Technical Summary
The existing building thermally insulated composite panels lack the functions of constant temperature, decoration and multiple synergies, and the mechanical properties are insufficient, making it difficult to meet the needs of indoor temperature regulation and interior decoration of exterior walls.
The heat storage decorative plate is combined with aerogel insulation gel layer. The heat storage decorative plate is made of phase change functional aggregate and has heat storage and decorative functions; the aerogel insulation gel layer has low thermal conductivity and high pulling The pull-out strength is formed by compounding with the heat storage decorative panel to form a composite sheet with constant temperature, heat insulation and decorative functions.
It realizes the constant temperature, heat insulation and decorative functions of composite sheets, has excellent mechanical properties, can effectively block heat insulation conduction and maintain indoor temperature balance.
Smart Images

Figure CN119390394A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a composite board and a preparation method thereof. Background Art
[0002] The construction industry consumes a lot of energy, and energy conservation and emission reduction in the construction industry is imminent. The use of high-performance thermal insulation materials is one of the important ways to reduce energy consumption.
[0003] Traditional building insulation materials can be roughly divided into organic insulation materials and inorganic insulation materials. Inorganic insulation materials have the advantage of fireproof performance, but there are problems such as thick insulation layer and easy cracking. Organic insulation materials have advantages such as good thermal insulation performance and waterproofness, but the fire resistance level is low, which limits their application. Aerogel's excellent properties such as light weight, heat insulation, fire resistance, and high temperature resistance make it advantageous in the field of building thermal insulation and have great potential in the field of building energy conservation, thermal insulation and fire prevention. However, traditional aerogel felt is difficult to popularize in the domestic construction market due to its inconvenient installation and high price. Aerogel board has high mechanical strength, but it only has thermal insulation performance and does not have a constant temperature effect.
[0004] Existing thermal insulation composite panels have thermal insulation properties but no other functions. If the panels are used in indoor buildings with high transparency, the temperature cannot be effectively regulated, which limits their application. Moreover, such panels cannot be fully applied to the outermost layer on the inside of the exterior wall and cannot have a decorative function, which is also one of the disadvantages of such panels.
[0005] In view of this, this invention is proposed. Summary of the invention
[0006] The first object of the present invention is to provide a composite board material which has the functions of constant temperature, heat insulation and decoration, can block the conduction of heat, maintain the indoor temperature balance, and has good mechanical properties.
[0007] The second object of the present invention is to provide a method for preparing a composite board, which has simple steps and is suitable for large-scale industrial production.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a composite board material, comprising: a heat storage decorative board and an aerogel thermal insulation gel layer arranged on the heat storage decorative board; the heat storage decorative board comprises a phase change functional aggregate.
[0010] Furthermore, the phase-change functional aggregate comprises aggregate and a phase-change material and an encapsulation material which sequentially encapsulate the aggregate;
[0011] The aggregate is mainly made of the following raw materials in parts by weight: 18 to 50 parts of tungsten tailings, 0.1 to 40 parts of diatomaceous earth, 8 to 16 parts of cement, 2 to 4 parts of quicklime, 4 to 6 parts of silica fume, 4 to 12 parts of gypsum, 18 to 30 parts of mineral powder, 1 to 6 parts of additives, 4 to 8 parts of fly ash and pigments;
[0012] The phase change material is mainly prepared from the following raw materials in parts by weight: 2 to 9 parts of lauric acid, 8 to 30 parts of palmitic acid and 4 to 6 parts of n-decanoic acid;
[0013] The packaging material is mainly prepared from the following raw materials in parts by weight: 1 to 2 parts of a coupling agent and 15 to 22 parts of a first emulsion.
[0014] Further, it includes at least one of the following features (1) to (3);
[0015] (1) The additive includes at least one of CaCl2, urea and triethanolamine;
[0016] (2) The coupling agent includes at least one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent and a bimetallic coupling agent;
[0017] (3) The first emulsion includes styrene acrylic emulsion and / or silicone acrylic emulsion.
[0018] Furthermore, the preparation method of the phase change functional aggregate comprises the following steps:
[0019] The various raw materials of the aggregate are mixed, granulated and cured in sequence to obtain the aggregate; the various raw materials of the phase change material are mixed to obtain the phase change material; the various raw materials of the packaging material are mixed to obtain the packaging material; the aggregate is soaked in the phase change material and the packaging material in sequence to obtain the phase change functional aggregate.
[0020] Furthermore, the heat storage decorative plate is mainly made of the following raw materials in parts by mass:
[0021] 20-28 parts of cement, 5-8 parts of metakaolin, 40-60 parts of quartz sand, 3-5 parts of the second emulsion, 0.5-2 parts of water reducing agent, 2-5 parts of water and 4-20 parts of the phase change functional aggregate.
[0022] Furthermore, the phase change functional aggregate comprises a first phase change functional aggregate and a second phase change functional aggregate in a mass ratio of 1:(2-4); the average particle size of the first phase change functional aggregate is 2-3 mm; the average particle size of the second phase change functional aggregate is 4-6 mm;
[0023] And / or, the second emulsion comprises a styrene-acrylate emulsion.
[0024] Furthermore, the method for preparing the heat storage decorative plate comprises the following steps:
[0025] The raw materials of the heat storage decorative board are mixed uniformly, and then pressed, shaped and steamed in sequence to obtain the heat storage decorative board.
[0026] Furthermore, the aerogel thermal insulation gel layer includes the following components in parts by mass: 100-280 parts of a third emulsion, 0.1-30 parts of aerogel, 100-200 parts of hollow glass microspheres, 15-35 parts of expanded perlite, 15-30 parts of fiber, 8-15 parts of additives and 100-180 parts of water.
[0027] Further, it includes at least one of the following features (1) to (4);
[0028] (1) The third emulsion comprises at least one of styrene acrylic emulsion, acrylic emulsion and silicone acrylic emulsion;
[0029] (2) The aerogel comprises a hydrophilic silica aerogel or a hydrophobic silica aerogel;
[0030] (3) The fiber comprises at least one of polypropylene fiber, glass fiber and basalt fiber;
[0031] (4) The auxiliary agent includes at least one of a wetting agent, a defoaming agent, a silane coupling agent and a thickener.
[0032] In a second aspect, the present invention also provides a method for preparing the composite plate material as described above, comprising the following steps;
[0033] The material of the aerogel heat-insulating gel layer is coated on the surface of the heat-storage decorative board to obtain the composite board.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The present invention uses phase-change functional aggregates with heat storage and decorative functions in a board to obtain a heat storage decorative board with heat storage and decorative functions and excellent mechanical properties; the raw material of the aerogel thermal insulation gel layer of the present invention can be used to prepare an aerogel thermal insulation gel layer with low thermal conductivity and high tensile strength; then the aerogel thermal insulation gel layer is combined with the heat storage decorative board to obtain a composite board with constant temperature, heat insulation and decorative functions in one and excellent mechanical properties, and the composite board can effectively form multiple synergistic effects, block heat conduction, and maintain indoor temperature balance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 It is a schematic diagram of the composite board of the present invention.
[0038] Figure 2 is a picture of the aggregate of the present invention.
[0039] Figure 3 This is a picture of the heat storage decorative panel of the present invention.
[0040] Figure 4 This is a DSC test chart of the phase change material of Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0042] A composite board and a preparation method thereof of the present invention are described in detail below.
[0043] See also Figure 1 In some embodiments of the present invention, a composite board is provided, comprising: a heat storage decorative board and an aerogel thermal insulation gel layer arranged on the heat storage decorative board; the heat storage decorative board comprises a phase change functional aggregate.
[0044] The composite board of the present invention is a composite board of aerogel thermal insulation gel layer and a heat storage decorative board to obtain a composite board with constant temperature, heat insulation and decorative functions and excellent mechanical properties. The board can effectively form multiple synergistic effects, block heat conduction, and maintain indoor temperature balance.
[0045] In some embodiments of the present invention, the thickness of the aerogel thermal insulation gel layer is 8 to 15 mm; the thickness of the heat storage decorative plate is 20 to 30 mm. The present invention does not strictly limit the thickness of the aerogel thermal insulation gel layer and the thickness of the heat storage decorative plate, and can be adjusted according to actual needs.
[0046] In some embodiments of the present invention, the phase-change functional aggregate comprises an aggregate and a phase-change material and an encapsulating material that sequentially encapsulate the aggregate;
[0047] The aggregate is mainly made of the following raw materials in parts by weight: 18-50 parts of tungsten tailings, 0.1-40 parts of diatomaceous earth, 8-16 parts of cement, 2-4 parts of quicklime, 4-6 parts of silica fume, 4-12 parts of gypsum, 18-30 parts of mineral powder, 1-6 parts of additives, 4-8 parts of fly ash and pigments;
[0048] The phase change material is mainly prepared from the following raw materials in parts by weight: 2 to 9 parts of lauric acid, 8 to 30 parts of palmitic acid and 4 to 6 parts of n-decanoic acid;
[0049] The packaging material is mainly prepared from the following raw materials in parts by weight: 1 to 2 parts of coupling agent and 15 to 22 parts of the first emulsion.
[0050] In some embodiments of the present invention, the additive includes at least one of CaCl2, urea and triethanolamine; the additive can adjust the hardening time.
[0051] In some embodiments of the present invention, the pigment includes but is not limited to at least one of titanium dioxide, iron oxide red S130, iron oxide blue, iron oxide green and iron oxide black.
[0052] In some embodiments of the present invention, the coupling agent includes at least one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent and a bimetallic coupling agent; the addition of the coupling agent is beneficial to enhancing the bonding force between the packaging material and the aggregate.
[0053] In some embodiments of the present invention, the first emulsion includes but is not limited to styrene acrylic emulsion and / or silicone acrylic emulsion.
[0054] In different embodiments of the present invention, in the raw materials of aggregate, the mass fraction of tungsten tailings can be 18 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts, etc.; the mass fraction of diatomaceous earth can be 0.1 parts, 10 parts, 20 parts, 30 parts or 40 parts, etc.; the mass fraction of cement can be 8 parts, 10 parts, 12 parts, 14 parts or 16 parts, etc.; the mass fraction of quicklime can be 2 parts, 3 parts or 4 parts, etc.; the mass fraction of silica ash can be 4 parts, 5 parts or 6 parts, etc.; the mass fraction of gypsum can be 4 parts, 8 parts or 12 parts, etc.; the mass fraction of mineral powder can be 18 parts, 20 parts, 25 parts or 30 parts, etc.; the mass fraction of additives can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, etc.; the mass fraction of fly ash can be 4 parts, 6 parts or 8 parts, etc.; the mass fraction of pigment can be adjusted according to color changes, for example, it can be 3 parts, 4 parts or 5 parts, etc.
[0055] In different embodiments of the present invention, in the raw materials of the phase change material, the mass fraction of lauric acid can be 2 parts, 5 parts or 9 parts, etc.; the mass fraction of palmitic acid can be 8 parts, 15 parts, 20 parts, 25 parts or 30 parts, etc.; the mass fraction of decanoic acid can be 4 parts, 5 parts or 6 parts, etc.
[0056] In different embodiments of the present invention, in the raw materials of the packaging material, the mass fraction of the coupling agent can be 1 part, 1.5 parts or 2 parts, etc.; the mass fraction of the first emulsion can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts or 22 parts, etc.
[0057] In some embodiments of the present invention, the method for preparing the phase change functional aggregate comprises the following steps:
[0058] The various raw materials of the aggregate are mixed, granulated and cured in sequence to obtain the aggregate; the various raw materials of the phase change material are mixed to obtain the phase change material; the various raw materials of the encapsulation material are mixed to obtain the encapsulation material; the aggregate is soaked in the phase change material and the encapsulation material in sequence to obtain the phase change functional aggregate.
[0059] In some embodiments of the present invention, the method for preparing the phase change functional aggregate specifically comprises the following steps:
[0060] Tungsten tailings, diatomaceous earth, cement, quicklime, silica fume, gypsum, mineral powder, additives, fly ash and pigment are mixed and stirred in a ball mill to obtain a cementitious material; the cementitious material is placed in a disc granulator, water is added by spraying, and after molding, curing is performed to obtain aggregate; preferably, the rotation speed of the disc granulator is 20-35r / min, and the inclination angle of the disc surface of the disc granulator to the horizontal ground is 48°-53°; preferably, the curing includes: initial curing at 15-30°C and relative humidity of 75%-100%, and then curing at 0.6-0.9MPa and 150-200°C;
[0061] After mixing lauric acid, palmitic acid and n-decanoic acid, the mixture is allowed to stand at 70-90° C. for 4-6 hours to obtain a phase change material; preferably, the mixture is allowed to stand in a sealed condition to avoid volatilization.
[0062] Mixing the coupling agent and the first emulsion to obtain a packaging material;
[0063] After the aggregate is immersed in the molten phase change material for 1 to 3 hours, it is taken out and then immersed in the packaging material for 1 to 5 minutes to obtain the phase change functional aggregate.
[0064] See also Figure 2 The method for preparing the phase-change functional aggregate of the present invention can be used to prepare spherical aggregates of different colors.
[0065] The present invention adopts a disc granulation method, takes tungsten tailings and diatomaceous earth as main raw materials, and cooperates with other raw materials to prepare aggregate with decorative properties, high cylinder pressure strength and adsorption rate; wherein, diatomaceous earth and tungsten tailings can not only reduce the aggregate cost, but diatomaceous earth has a porous structure, can effectively improve the water absorption rate of the aggregate, can effectively adsorb the phase change material, and improve the adsorption of the phase change material; the addition of silica fume and quicklime can adjust the calcium-silicon ratio of the overall material, and can generate tobermorite in an autoclaved environment. Mullite is a hard phase substance and can improve the overall strength of the aggregate.
[0066] The present invention prepares a phase change material with a comfortable temperature for human body by melt blending method. The phase change interval of the phase change material is 32-40°C, the phase change starting temperature is 32°C, and the ending temperature is 40°C.
[0067] In order to highlight the phase change constant temperature range of the phase change aggregate, the present invention needs to increase the content of the phase change material as much as possible. However, the increase in water absorption will reduce the cylinder compressive strength. The present invention increases the water absorption without significantly reducing the cylinder compressive strength by adding diatomaceous earth and other raw materials. A phase change functional aggregate with heat storage, modification and pressure bearing is prepared, which can be used as an indoor wall decoration board. The different colors of the phase change functional aggregate can serve as an embellishment and can also be used for floor panels.
[0068] See also Figure 3In some embodiments of the present invention, the heat storage decorative plate is mainly made of the following raw materials in parts by mass:
[0069] 20-28 parts of cement, 5-8 parts of kaolin, 40-60 parts of quartz sand, 3-5 parts of the second emulsion, 0.5-2 parts of water reducer, 2-3 parts of water and 4-20 parts of phase change functional aggregate.
[0070] In different embodiments of the present invention, among the raw materials of the heat storage decorative panel, the mass fraction of cement can be 20 parts, 22 parts, 24 parts, 26 parts or 28 parts, etc.; the mass fraction of kaolin can be 5 parts, 6 parts, 7 parts or 8 parts, etc.; the mass fraction of quartz sand can be 40 parts, 45 parts, 50 parts, 55 parts or 60 parts, etc.; the mass fraction of the second emulsion can be 3 parts, 4 parts or 5 parts, etc.; the mass fraction of the water reducer can be 0.5 parts, 1 parts or 2 parts, etc.; the mass fraction of water can be 2 parts or 3 parts, etc.; the mass fraction of the phase change functional aggregate can be 4 parts, 8 parts, 12 parts, 16 parts or 20 parts, etc.
[0071] In some embodiments of the present invention, the quartz sand includes quartz sand with a particle size of 40 to 60 mesh, quartz sand with a particle size of 60 to 80 mesh, and quartz sand with a particle size of 80 to 120 mesh in a mass ratio of (6 to 13): (5 to 10): (13 to 25).
[0072] In some embodiments of the present invention, the phase change functional aggregate includes a first phase change functional aggregate and a second phase change functional aggregate in a mass ratio of 1:(2-4); the average particle size of the first phase change functional aggregate is 2-3 mm; the average particle size of the second phase change functional aggregate is 4-6 mm; typically but not limitatively, for example, the mass ratio of the first phase change functional aggregate to the second phase change functional aggregate can be 1:2, 1:3 or 1:4, etc.
[0073] Phase-change functional aggregates with a single particle size can easily reduce the flexural resistance of the resulting board. The present invention uses a mixture of the above two particle sizes of phase-change functional aggregates to improve the flexural resistance of the board and can also be matched in color.
[0074] In some embodiments of the present invention, the second emulsion includes, but is not limited to, a styrene-acrylate emulsion.
[0075] In some embodiments of the present invention, the water reducer includes but is not limited to a polycarboxylate water reducer.
[0076] In some embodiments of the present invention, a method for preparing a heat storage decorative plate comprises the following steps:
[0077] The raw materials of the heat storage decorative board are mixed uniformly, pressed, shaped and steamed in sequence to obtain the heat storage decorative board.
[0078] In some embodiments of the present invention, the method for preparing the heat storage decorative plate specifically comprises the following steps:
[0079] After cement, metakaolin, quartz sand, the second emulsion and phase change functional aggregate are mixed, the water reducer is mixed with water and added in batches, and the mixture is poured into a mold. The mold is pressed and shaken for 80 to 120 seconds at a vacuum degree of 0.1 MPa and a cylinder pressure of 0.1 to 0.5 MPa. After pressing and molding, the mold is placed in an environment of 20°C and 90% humidity for 24 to 48 hours. After the shape is fixed, the mold is placed in a steam curing box at 80 to 90°C for 30 to 48 hours to obtain a heat storage decorative board.
[0080] The present invention uses a pressing molding method and a phase change functional aggregate to prepare a constant temperature heat storage decorative board with certain mechanical properties. The board uses the phase change functional aggregate to replace quartz sand. Quartz sand is a high-priced raw material. The present invention uses the phase change functional aggregate to replace the quartz sand raw material, which can effectively reduce the preparation cost. The traditional board only has a certain heat insulation effect, while the board filled with the phase change functional aggregate has a phase change heat storage function, the phase change starting temperature is 32°C, and the ending temperature is 40°C, which can effectively resist high temperature extreme weather. Phase change functional aggregates of different colors can play an embellishment role, giving the board a decorative function. Through the coordination of various components, the use of phase change functional aggregates to replace quartz sand has no obvious effect on the mechanical properties of the board, and the flexural strength and compressive strength of the board fully meet the requirements of GB / T35160-2017 "Test Methods for Synthetic Stone".
[0081] In some embodiments of the present invention, the aerogel thermal insulation gel layer includes the following components, measured by weight: 100-280 parts of a third emulsion, 0.1-30 parts of aerogel, 100-200 parts of hollow glass microspheres, 15-35 parts of expanded perlite, 15-30 parts of fiber, 8-15 parts of additives and 100-150 parts of water.
[0082] In some embodiments of the present invention, the aerogel thermal insulation gel layer further includes: white carbon black; preferably, the mass fraction of white carbon black is 10 to 20 parts; specifically, the aerogel thermal insulation gel layer includes the following components in mass fractions: 100 to 280 parts of the third emulsion, 0.1 to 30 parts of aerogel, 100 to 200 parts of hollow glass microspheres, 15 to 35 parts of expanded perlite, 10 to 20 parts of white carbon black, 15 to 30 parts of fibers, 8 to 15 parts of additives and 100 to 150 parts of water.
[0083] In some embodiments of the present invention, the third emulsion includes at least one of styrene acrylic emulsion, acrylic emulsion and silicone acrylic emulsion.
[0084] In some embodiments of the present invention, the aerogel includes hydrophilic silica aerogel or hydrophobic silica aerogel; the main component of the aerogel is SiO2, the hydrophilic silica aerogel has hydroxyl groups on the surface of SiO2, and the hydrophobic silica aerogel has alkyl groups on the surface.
[0085] In some embodiments of the present invention, the particle size of the hollow vitrified microspheres is 40-100 meshes.
[0086] Hollow vitrified microspheres and expanded perlite are thermal insulation materials, and white carbon black can adjust the thermal conductivity of the gel.
[0087] In some embodiments of the present invention, the fiber includes at least one of polypropylene fiber, glass fiber, basalt fiber and aluminum silicate fiber; the fiber can adjust the anti-cracking performance of the gel.
[0088] In some embodiments of the present invention, the auxiliary agent includes at least one of a wetting agent, a defoaming agent, a silane coupling agent and a thickener.
[0089] In some embodiments of the present invention, the wetting agent includes at least one of silicones, polyether-modified silicones, and ethylene oxide adducts.
[0090] In some embodiments of the present invention, the defoaming agent includes at least one of polydimethylsiloxane, tributyl phosphate, and a siloxane ether copolymer.
[0091] In some embodiments of the present invention, the silane coupling agent includes KH-550 and / or KH-560.
[0092] In some embodiments of the present invention, the thickener includes at least one of carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl methyl cellulose.
[0093] In some embodiments of the present invention, a method for preparing an aerogel thermal insulation gel layer comprises the following steps:
[0094] The emulsion, the defoamer, the silane coupling agent, the wetting agent, the thickener and water are mixed and stirred to obtain a mixture A;
[0095] Premixing aerogel, hollow vitrified microspheres, expanded perlite and fibers to obtain a mixture B;
[0096] Mixing mixture A and mixture B to obtain aerogel thermal insulation gel;
[0097] The aerogel thermal insulation gel is coated on the surface of the heat storage decorative plate to obtain an aerogel thermal insulation gel layer.
[0098] Aerogel has low thermal conductivity, light weight, and high heat resistance, and is currently known to be a relatively good thermal insulation material. Compared with traditional thermal insulation materials, the aerogel thermal insulation gel prepared with aerogel as the main filler in the present invention has excellent construction performance, lower thermal conductivity, and higher tensile strength.
[0099] The present invention prepares a composite board with the ability to resist extreme weather by compounding aerogel thermal insulation gel with a heat storage decorative board; in addition to thermal insulation performance, the board also has decorative and temperature regulation functions, and is an interior wall functional board with great market potential.
[0100] The phase change temperature of phase change materials has a certain range, and the amount of heat they absorb has an upper limit, so their application under extremely high temperatures is limited. The present invention combines aerogel insulation gel with low thermal conductivity and high tensile strength with a heat storage decorative panel to obtain a composite panel with constant temperature, heat insulation and decorative functions and meeting certain mechanical strength requirements. The panel can effectively form multiple synergistic effects, block heat conduction, and maintain indoor temperature balance.
[0101] Most gel products have excellent thermal insulation performance, but the bonding strength with other materials is poor and they are easy to fall off. The aerogel thermal insulation gel of the present invention has excellent bonding strength and thermal insulation performance. The composite board prepared by compounding with the heat storage decorative board has the functions of decoration, thermal insulation and temperature regulation, and meets certain mechanical strength requirements.
[0102] In some embodiments of the present invention, a method for preparing a composite plate material is also provided, comprising the following steps:
[0103] The material of the aerogel thermal insulation gel layer is coated on the surface of the heat storage decorative board to obtain a composite board.
[0104] Example 1
[0105] The method for preparing the composite plate provided in this embodiment comprises the following steps:
[0106] S1. 26 parts of tungsten tailings, 30 parts of diatomaceous earth, 10 parts of cement, 2.5 parts of quicklime, 4.5 parts of silica fume, 6 parts of gypsum, 21 parts of mineral powder, 2 parts of CaCl2, 2 parts of urea, 2 parts of triethanolamine, 6 parts of fly ash and 4 parts of pigment (iron oxide red S130) were mixed and stirred in a ball mill for 10 minutes to obtain a cementitious material;
[0107] The above-mentioned cementitious material is placed in a disc granulator, the rotation speed is set to 20-35 r / min, the disc surface of the disc granulator is inclined at an angle of 53° to the horizontal ground, water is added in a spraying manner during the operation of the disc granulator, and the total water mass to cementitious material mass ratio is 1:8, and it is taken out after being formed; then curing is performed, and initial curing is performed at 15-30° C. and relative humidity of 75%-100%, and then curing is performed at 0.6-0.9 MPa and 150-200° C. to obtain aggregate;
[0108] 3 parts of lauric acid, 15 parts of palmitic acid and 4 parts of n-decanoic acid were placed in a beaker, and the beaker was placed in a constant temperature water bath at 80°C for 5 hours to obtain a phase change material; a DSC test was performed on the phase change material, and the results are as follows: Figure 4 As shown;
[0109] Mix 1 part of coupling agent and 18 parts of emulsion to obtain packaging material;
[0110] The aggregate is immersed in the molten phase change material and allowed to stand for 2 hours; after being taken out, it is immersed in the packaging material for 2 minutes to obtain the phase change functional aggregate.
[0111] S2, 24.6 parts of cement, 6.2 parts of kaolin, 55.8 parts of quartz sand, 4.3 parts of styrene-acrylate emulsion and 4.5 parts of phase change functional aggregate are placed in a stirring pot and stirred, 1.3 parts of polycarboxylate water reducer and 3.1 parts of water are mixed and added in batches, and the stirring time is 15 minutes; the stirred raw materials are poured into a mold, the vacuum degree is set to 0.1MPa, the cylinder pressure is set to 0.1-0.5MPaMPa, and the pressing and shaking is performed for 80-120s; after pressing and molding, it is placed in an environment of 20°C and 90% humidity for 24h, and after shaping, it is placed in a 90°C steam curing box for 48h to obtain a heat storage decorative board;
[0112] The quartz sand is obtained by mixing quartz sand with a particle size of 40 to 60 meshes, quartz sand with a particle size of 60 to 80 meshes, and quartz sand with a particle size of 80 to 100 meshes in a mass ratio of 17.3:11:27.5;
[0113] The phase change functional aggregate is obtained by mixing a phase change functional aggregate with an average particle size of 2.36 mm and a phase change functional aggregate with an average particle size of 4.75 mm in a mass ratio of 1.3:3.2.
[0114] S3, 150 parts of styrene-acrylic emulsion, 2 parts of defoaming agent (polydimethylsiloxane), 5 parts of silane coupling agent (KH-550), 2 parts of wetting agent (polyether-modified silicone), 4 parts of thickener (hydroxyethyl cellulose) and 150 parts of water were mixed and stirred to obtain a mixture A;
[0115] Premix 5 parts of hydrophobic silica aerogel, 200 parts of hollow vitrified microspheres, 15 parts of expanded perlite and 20 parts of aluminum silicate fibers to obtain a mixture B;
[0116] The mixture A and the mixture B are stirred in a stirring pot at a speed of 200 to 400 rpm for 30 to 90 seconds to obtain an aerogel thermal insulation gel;
[0117] S4. Apply the aerogel thermal insulation gel on a 30 mm thick heat storage decorative board by scraping with a thickness of 10 mm to obtain a composite board.
[0118] Example 2
[0119] The preparation method of the composite board provided in this embodiment refers to that in embodiment 1, the only difference is that in step S1, the mass fraction of diatomaceous earth is 10 parts.
[0120] Example 3
[0121] The preparation method of the composite board provided in this embodiment refers to that in embodiment 1, the only difference is that in step S1, the mass fraction of diatomaceous earth is 20 parts.
[0122] Example 4
[0123] The preparation method of the composite board provided in this embodiment refers to that in Embodiment 1, except that, in step S1, the mass fraction of diatomaceous earth is 40 parts.
[0124] Example 5
[0125] The preparation method of the composite board provided in this embodiment refers to Example 1, with the only difference being that in step S2, the mass fraction of quartz sand is 51.2 parts, and the quartz sand is obtained by mixing quartz sand with a particle size of 40-60 mesh, quartz sand with a particle size of 60-80 mesh, and quartz sand with a particle size of 80-100 mesh in a mass ratio of 16:11.1:24.2; the mass fraction of phase change functional aggregate is 9.1 parts, and the phase change functional aggregate is obtained by mixing phase change functional aggregate with an average particle size of 2.36 mm and phase change functional aggregate with an average particle size of 4.75 mm in a mass ratio of 2.7:6.4.
[0126] Example 6
[0127] The preparation method of the composite board provided in this embodiment refers to Example 1, with the only difference being that in step S2, the mass fraction of quartz sand is 46.7 parts, and the quartz sand is obtained by mixing quartz sand with a particle size of 40-60 mesh, quartz sand with a particle size of 60-80 mesh, and quartz sand with a particle size of 80-100 mesh in a mass ratio of 12.5:10.2:24.0; the mass fraction of phase change functional aggregate is 13.7 parts, and the phase change functional aggregate is obtained by mixing phase change functional aggregate with an average particle size of 2.36 mm and phase change functional aggregate with an average particle size of 4.75 mm in a mass ratio of 4.1:9.6.
[0128] Example 7
[0129] The preparation method of the composite board provided in this embodiment refers to Example 1, with the only difference being that in step S2, the mass fraction of quartz sand is 42.1 parts, and the quartz sand is obtained by mixing quartz sand with a particle size of 40-60 mesh, quartz sand with a particle size of 60-80 mesh, and quartz sand with a particle size of 80-100 mesh in a mass ratio of 13.0:9.3:21.7; the mass fraction of phase change functional aggregate is 18.2 parts, and the phase change functional aggregate is obtained by mixing phase change functional aggregate with an average particle size of 2.36 mm and phase change functional aggregate with an average particle size of 4.75 mm in a mass ratio of 5.5:12.7.
[0130] Example 8
[0131] The preparation method of the composite board provided in this embodiment refers to Example 1, except that, in step S3, 150 parts of styrene-acrylic emulsion, 2 parts of defoaming agent (polydimethylsiloxane), 5 parts of silane coupling agent (KH-550), 2 parts of wetting agent (ethylene oxide adduct), 4 parts of thickener (hydroxyethyl cellulose) and 150 parts of water are mixed and stirred to obtain a mixture A; 10 parts of hydrophobic silica aerogel, 200 parts of hollow glass microspheres, 10 parts of expanded perlite and 20 parts of polypropylene fiber are premixed to obtain a mixture B; mixture A and mixture B are stirred in a stirring pot at a speed of 200 to 400 rpm for 30 to 90 seconds to obtain an aerogel thermal insulation gel.
[0132] Example 9
[0133] The preparation method of the composite board provided in this embodiment refers to Example 1, except that, in step S3, 150 parts of styrene-acrylic emulsion, 2 parts of defoaming agent (polydimethylsiloxane), 5 parts of silane coupling agent (KH-550), 2 parts of wetting agent (organic silicon), 4 parts of thickener (hydroxyethyl cellulose) and 160 parts of water are mixed and stirred to obtain a mixture A; 10 parts of hydrophilic silica aerogel, 200 parts of hollow glass microspheres, 10 parts of expanded perlite and 20 parts of basalt fiber are premixed to obtain a mixture B; mixture A and mixture B are stirred in a stirring pot at a speed of 200 to 400 rpm for 30 to 90 seconds to obtain an aerogel thermal insulation gel.
[0134] Example 10
[0135] The preparation method of the composite board provided in this embodiment refers to Example 1, except that, in step S3, 170 parts of styrene-acrylic emulsion, 2 parts of defoaming agent (tributyl phosphate), 10 parts of white carbon black, 5 parts of silane coupling agent (KH-550), 2 parts of wetting agent (ethylene oxide adduct), 4 parts of thickener (hydroxyethyl cellulose) and 180 parts of water are mixed and stirred to obtain a mixture A; 10 parts of hydrophobic silica aerogel, 200 parts of hollow glass microspheres, 20 parts of expanded perlite and 20 parts of polypropylene fiber are premixed to obtain a mixture B; mixture A and mixture B are stirred in a stirring pot at a speed of 200 to 400 rpm for 30 to 90 seconds to obtain an aerogel thermal insulation gel.
[0136] Embodiment 11
[0137] The preparation method of the composite board provided in this embodiment refers to Example 1, except that, in step S3, 130 parts of silicone-acrylic emulsion, 2 parts of defoaming agent (tributyl phosphate), 6 parts of silane coupling agent (KH-560), 6 parts of wetting agent (polyether-modified silicone), 7 parts of thickener (hydroxyethyl cellulose) and 140 parts of water are mixed and stirred to obtain a mixture A; 10 parts of hydrophobic silica aerogel, 200 parts of hollow glass microspheres, 10 parts of expanded perlite and 20 parts of glass fiber are premixed to obtain a mixture B; mixture A and mixture B are stirred in a stirring pot at a speed of 200 to 400 rpm for 30 to 90 seconds to obtain an aerogel thermal insulation gel.
[0138] Comparative Example 1
[0139] The preparation method of the composite board provided in this comparative example refers to Example 1, except that diatomaceous earth is not added in step S1.
[0140] Comparative Example 2
[0141] The preparation method of the composite board provided in this comparative example refers to Example 1, except that, in step S3, 150 parts of styrene-acrylic emulsion, 2 parts of defoaming agent (polydimethylsiloxane), 6 parts of silane coupling agent (KH-550), 2 parts of wetting agent (polyether-modified silicone), 4 parts of thickener (hydroxypropyl fiber) and 150 parts of water are mixed and stirred to obtain a mixture A; 200 parts of hollow glass microspheres, 30 parts of expanded perlite and 20 parts of glass fiber are premixed to obtain a mixture B; mixture A and mixture B are stirred in a stirring pot at a speed of 200 to 400 rpm for 30 to 90 s to obtain an aerogel thermal insulation gel.
[0142] Comparative Example 3
[0143] The preparation method of the composite board provided in this comparative example refers to Example 1, except that, in step S3, 130 parts of silicone-acrylic emulsion, 2 parts of defoaming agent (silicone ether copolymer), 6 parts of silane coupling agent (KH-560), 2 parts of wetting agent (polyether-modified silicone), 4 parts of thickener (hydroxymethyl cellulose) and 130 parts of water are mixed and stirred to obtain a mixture A; 5 parts of hydrophobic silica aerogel, 200 parts of hollow glass microspheres, 10 parts of expanded perlite and 20 parts of glass fiber are premixed to obtain a mixture B; mixture A and mixture B are stirred in a stirring pot at a speed of 200 to 400 rpm for 30 to 90 s to obtain an aerogel thermal insulation gel.
[0144] Test Example 1
[0145] The cylinder compressive strength and water absorption of the aggregates of Examples 1 to 4 and Comparative Example 1 were tested, and the results are shown in Table 1.
[0146] The cylinder pressure strength and water absorption tests are carried out in accordance with T / CECS10113-2020 "High-strength Lightweight Aggregate", and the water absorption test time is 1h.
[0147] Table 1
[0148] Diatomaceous earth (part) Cylinder compressive strength (MPa) Water absorption (%) Example 2 10 17.3 8.3 Example 3 20 16.3 12.4 Example 1 30 13.4 16.6 Example 4 40 8.2 22.3 Comparative Example 1 0 18.3 6.8
[0149] It can be seen from Table 1 that the aggregate of the present invention has both high cylinder pressure strength and adsorption rate.
[0150] The bending strength and compressive strength of the heat storage decorative panels of Example 1 and Examples 5 to 8 were tested, and the results are shown in Table 2.
[0151] Test method: Test according to the bending strength and compressive strength test methods in the national standard GB / T 35160-2017 "Synthetic Stone Test Methods".
[0152] Table 2
[0153] Bending strength(MPa) Compression strength(MPa) Example 1 14.2 40.2 Example 5 13.7 35.6 Example 6 13.2 32.6 Example 7 12.5 42.3
[0154] It can be seen from Table 2 that the heat storage decorative panel of the present invention has excellent mechanical properties.
[0155] The thermal conductivity and surface drying time of the aerogel thermal insulation gels of Example 1, Examples 8 to 11, Comparative Example 2, and Comparative Example 3 were tested, and the results are shown in Table 3.
[0156] The test method for thermal conductivity is: test the thermal conductivity at 25°C in accordance with GB / T 10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Heat Flow Meter Method".
[0157] The test method for surface drying time is: Determine the surface drying time in accordance with GB / T 1728-2020 "Determination of Drying Time of Paint Film and Putty Film".
[0158] Table 3
[0159] Thermal conductivity W / (m·k) Surface drying time (h) Example 1 0.035 5 Example 8 0.027 4 Example 9 0.035 4 Example 10 0.025 3 Embodiment 11 0.031 5 Comparative Example 2 0.059 5 Comparative Example 3 0.037 4
[0160] It can be seen from Table 3 that the aerogel thermal insulation gel of the present invention has a lower thermal conductivity.
[0161] The pull-out strength of the composite plates of Example 1, Examples 8 to 11, Comparative Example 2, and Comparative Example 3 were tested, and the results are shown in Table 4.
[0162] Pull-out strength test method: Determined in accordance with JG / T 157 "Exterior Wall Putty for Building".
[0163] Table 4
[0164] Tensile strength (MPa) Example 1 0.92 Example 8 0.63 Example 9 0.75 Example 10 1.02 Embodiment 11 0.70 Comparative Example 2 1.12 Comparative Example 3 0.65
[0165] It can be seen from Table 4 that the composite board of the present invention has excellent thermal insulation performance and good tensile strength.
[0166] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite sheet, characterized in that: include: A heat storage decorative plate and an aerogel thermal insulation gel layer arranged on the heat storage decorative plate; the heat storage decorative plate comprises a phase change functional aggregate.
2. The composite sheet material according to claim 1, characterized in that: The phase-change functional aggregate comprises aggregate and a phase-change material and an encapsulation material which encapsulate the aggregate in sequence; The aggregate is mainly made of the following raw materials in parts by weight: 18 to 50 parts of tungsten tailings, 0.1 to 40 parts of diatomaceous earth, 8 to 16 parts of cement, 2 to 4 parts of quicklime, 4 to 6 parts of silica fume, 4 to 12 parts of gypsum, 18 to 30 parts of mineral powder, 1 to 6 parts of additives, 4 to 8 parts of fly ash and pigments; The phase change material is mainly prepared from the following raw materials in parts by weight: 2 to 9 parts of lauric acid, 8 to 30 parts of palmitic acid and 4 to 6 parts of n-decanoic acid; The packaging material is mainly prepared from the following raw materials in parts by weight: 1 to 2 parts of a coupling agent and 15 to 22 parts of a first emulsion.
3. The composite sheet material according to claim 2, characterized in that: The method comprises at least one of the following features (1) to (3); (1) The additive includes at least one of CaCl2, urea and triethanolamine; (2) The coupling agent includes at least one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent and a bimetallic coupling agent; (3) The first emulsion includes styrene acrylic emulsion and / or silicone acrylic emulsion.
4. The composite sheet material according to claim 2, characterized in that: The preparation method of the phase change functional aggregate comprises the following steps: The various raw materials of the aggregate are mixed, granulated and cured in sequence to obtain the aggregate; the various raw materials of the phase change material are mixed to obtain the phase change material; the various raw materials of the packaging material are mixed to obtain the packaging material; the aggregate is soaked in the phase change material and the packaging material in sequence to obtain the phase change functional aggregate.
5. The composite sheet material according to claim 2, characterized in that: The heat storage decorative plate is mainly made of the following raw materials in parts by mass: 20-28 parts of cement, 5-8 parts of metakaolin, 40-60 parts of quartz sand, 3-5 parts of the second emulsion, 0.5-2 parts of water reducing agent, 2-5 parts of water and 4-20 parts of the phase change functional aggregate.
6. The composite sheet material according to claim 5, characterized in that: The phase change functional aggregate comprises a first phase change functional aggregate and a second phase change functional aggregate in a mass ratio of 1:(2-4); the average particle size of the first phase change functional aggregate is 2-3 mm; the average particle size of the second phase change functional aggregate is 4-6 mm; And / or, the second emulsion comprises a styrene-acrylate emulsion.
7. The composite sheet material according to claim 5, characterized in that: The method for preparing the heat storage decorative plate comprises the following steps: The raw materials of the heat storage decorative board are mixed uniformly, and then pressed, shaped and steamed in sequence to obtain the heat storage decorative board.
8. The composite sheet material according to claim 5, characterized in that: The aerogel thermal insulation gel layer comprises the following components by weight: 100-280 parts of a third emulsion, 0.1-30 parts of aerogel, 100-200 parts of hollow glass microspheres, 15-35 parts of expanded perlite, 15-30 parts of fiber, 8-15 parts of additives and 100-180 parts of water.
9. The composite sheet material according to claim 8, characterized in that: The method comprises at least one of the following features (1) to (4); (1) The third emulsion includes at least one of styrene acrylic emulsion, acrylic emulsion and silicone acrylic emulsion; (2) The aerogel comprises a hydrophilic silica aerogel or a hydrophobic silica aerogel; (3) The fiber comprises at least one of polypropylene fiber, glass fiber and basalt fiber; (4) The auxiliary agent includes at least one of a wetting agent, a defoaming agent, a silane coupling agent and a thickener.
10. The method for preparing a composite plate according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: The material of the aerogel heat-insulating gel layer is coated on the surface of the heat-storage decorative board to obtain the composite board.